BU PENDERITA SKIZOFRENIA DAN DAMPAKNYA TERHADAP HADANAH DALAM PERSPEKTIF ISLAM - Saimima, Salma (TAHKIM, 2014)
Hadanah is an authority to care and educate children who have not mumayiz (immature) or adults who have lost their thinking intelligence. The authority is more appropriate possessed by a women (mothers). Because the female instinct is more appropriate to care and educate children and her patience in dealing with the children life problems is higher than the patience of a man (father). Although both parents, especially the mother has authority and responsibility in hadanah, but in the Islamic perspective, a mother with schizophrenia is considered have not authority and responsibility to carry out hadanah for his children. Since people with schizophrenia have not the legal capacity to care and educate her children. Key words: Schizophrenia, hadanah, Islamic perspective